Influence of relative strength on the optimal load of the hang power clean and hang high pull in collegiate athletes - Xie, Yongmin; Pan, Xingyu; Peng, Fan; Sun, Qinchang (Frontiers in Sports and Active Living, 2025)
BackgroundAlthough training load is a critical determinant of adequate training stimuli for athletes, the optimal load for power training varies across individuals, and the underlying factors contributing to this variability remain unclear.ObjectiveThis study investigated the influence of relative strength on optimal load during the execution of the hang power clean (HPC) and hang high pull (HHP) among college athletes.MethodsA total of 30 male college athletes (mean ± standard deviation age, 21.8 ± 2.3 years) performed hang power cleans (HPCs) and hang high pulls (HHPs) on a three-dimensional force plate at loads corresponding to 45%, 65%, 80%, and 95% of their one-repetition maximum (1RM), presented in a randomized and counterbalanced order. The relationship between optimal load and relative strength was assessed using Pearson's correlation coefficient.ResultsThe optimal load for achieving maximum output power in the hang high pull (HPP) and hang power clean (HPC) exhibited a highly individualized characteristic.A significant positive correlation was found between athlete strength and optimal load for both the HPC (r = 0.478, P < .01) and HHP (r = 0.611, P < .001).ConclusionsA positive correlation between optimal load and the relative strength of the athlete for the HPC and the HHP indicated that as the athlete's strength increased, the load intensity should be appropriately increased to maintain efficient training stimulation to elicit maximum power for each athlete. However, this study did not examine female collegiate athletes and other athletic populations. coaches should be discreetly when applying this conclusion to these athletic groups.